DESENTRALISASI PENGELOLAAN WILAYAH PESISIR DAN LAUTAN DALAM KERANGKA PRINSIP NEGARA KEPULAUAN - Dhiana Puspitawati (Arena Hukum, 2014)
AbstractThe development of ocean management emerged during the United Nations Conference on Environment and Development 1992 (UNCED). UNCED produced what known as Rio Declaration, which introduced a wider, sustainable and integrated approach in managing the environment and this includes ocean space. As a result, Indonesia has produced Indonesian Act 32/2004 on Regional Autonomy, which devolves the management of coastal zone to provincial administration u/p to 12 nautical miles from the coastal shoreline, and one-third of the provincial administration is under local government administration. Further development was the enactment of Indonesian Act 27/2007 on the Management of Coastal Areas and Small Islands, which provides regulations on coastal areas zoning which will be conducted by regional as well as local government. This paper will analyse the legal conformity between national law on coastal management (as regulated under Act 32/2004 and Act 27/2007) with archipelagic states principles provided by international law (Part IV of the Law of the Sea Convention 1982). It is argued that the ground norm of archipelagic state principles was restoring the function of the ocean as unifying factor of Indonesian people for optimal utilization of ocean resources. On the other hand, the implementation of Act 32/2004 and Act 27/2007 raised conflicts, especially conflicts between traditional fishermen, which transform the function of the ocean as dividing factor of Indonesian people. Thus, it is argued that in ocean management more emphasized on the groun norm of archipelagic state principles should be done. In addition, a new system and corresponding sets of values for policy formulation and implementation must be created.  Key words: integrated, sustainability, decentralized coastal zone management, archipelagic state AbstrakPerkembangan pengelolaan wilayah laut dimulai pada saat diadakannya United Nations Conference on Environment and Development (UNCED) pada tahun 1992. UNCED menghasilkan Deklarasi Rio (Rio Declaration) berisi tentang prinsip-prinsip pengaturan serta pengelolaan wilayah laut modern, dimana diakui adanya pendekatan baru yang mengedepankan prinsip keterpaduan (integrated) dan keberlangsungan (sustainability) dalam pengelolaan wilayah laut.  Sehubungan dengan hal tersebut, Indonesia mengeluarkan Undang-Undang Nomor 32 Tahun 2004 tentang Pemerintahan Daerah (UU 32/2004), yang memberikan kewenangan pengelolaan wilayah pesisir dan lautan sebesar maksimal 12 mil laut kepada pemerintah propinsi, sedangkan pemerintah kabupaten/kota diberi kewenangan pengelolaan wilayah pesisir dan lautan sebesar 1/3 wilayah pesisir yang diberikan kepada pemerintah propinsi. Selanjutnya Undang-Undang Nomor 27 Tahun 2007 tentang Pengelolaan Wilayah Pesisir dan Pulau-Pulau Kecil mengatur tentang zonasi wilayah pesisir yang harus dilakukan oleh pemerintah daerah.Tulisan ini akan menganalisa kesesuaian norma hukum antara UU 32/2004 serta UU 27/2007, dengan prinsip negara kepulauan yang diatur dalam ketentuan hukum internasional. Norma dasar prinsip negara kepulauan adalah mengembalikan fungsi laut di Indonesia sebagai sarana pemersatu bangsa guna pemanfaatan sumber daya laut secara optimal untuk kepentingan bersama secara merata. Sementara itu pelaksanaan UU 32/2004 dan UU 27/2007 memunculkan banyak konflik, terutama konflik antar nelayan yang mengarah kepada berubahnya fungsi laut di Indonesia, bukan lagi sebagai sarana pemersatu melainkan sebagai sarana pemisah. Dengan demikian, dalam pelaksanaan desentralisasi pengelolaan wilayah pesisir dan lautan diperlukan suatu penekanan pada nilai-nilai dan norma yang melandasi prinsip negara kepulauan; serta diperlukan suatu mekanisme tersendiri yang dapat meminimalisir munculnya konflik. Kata kunci: integrated, sustainibilty, desentralisasi pengelolaan wilayah pesisir dan lautan, prinsip negara kepulauan